If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + -1h)(x + h) = 30 Reorder the terms: (9 + -1h)(h + x) = 30 Multiply (9 + -1h) * (h + x) (9(h + x) + -1h * (h + x)) = 30 ((h * 9 + x * 9) + -1h * (h + x)) = 30 ((9h + 9x) + -1h * (h + x)) = 30 (9h + 9x + (h * -1h + x * -1h)) = 30 Reorder the terms: (9h + 9x + (-1hx + -1h2)) = 30 (9h + 9x + (-1hx + -1h2)) = 30 Reorder the terms: (9h + -1hx + -1h2 + 9x) = 30 (9h + -1hx + -1h2 + 9x) = 30 Solving 9h + -1hx + -1h2 + 9x = 30 Solving for variable 'h'. Reorder the terms: -30 + 9h + -1hx + -1h2 + 9x = 30 + -30 Combine like terms: 30 + -30 = 0 -30 + 9h + -1hx + -1h2 + 9x = 0 The solution to this equation could not be determined.
| 26+2(3x+11)=-18x | | (9+h)(X+h)=30 | | 3-4x-9x=-3 | | 4(4x-3)=2(8x+8) | | (4m+5n)(4m-5m)= | | 5(x-4)=7(x-2) | | 4x+5=-(x-20) | | 3+3n-2=9n+33-2n | | x^2-6x=-4 | | x^2-36x+25=0 | | 4(2z-1)-3(z+4)=3(z+1) | | 3x^2-24x=27 | | 4(2z-1)-3(z+4)=4(z+1) | | -4x^2-6x+23=0 | | -4x^2+2x+23=0 | | x^2+8x+16=49 | | 64x^2-64=36 | | 5x-11x=30 | | y=2x^2+4x-30 | | x^2+12x+36=49 | | 5p+8=4p+12 | | a-2=5 | | 6(3z-1)-5(z+7)=2(z+1) | | x-7.7=-4.8 | | 6(3z-1)-5(z+7)=2(2+1) | | t+13=39 | | 14t+4(1-4t)= | | 2x-3(x+2)=-8 | | 2(x+3)+4x=3(x+1) | | 3x+22=50 | | 9x+4+3x+6= | | 4x-(4-x)=5x |